Incorporating algorithms into mathematics syllabus - Orhani, Senad (Trigin Institute, 2025)
In the digital age, developing algorithmic thinking skills has become particularly important for preparing students for the challenges of the 21st century. This study examines the potential of including algorithms and coding basics in mathematics syllabus, with the aim of improving students’ logical, analytical, and creative skills. Despite the increasing reliance on technology and automation in modern industries, many school curricula still focus on conventional mathematical problem-solving techniques without incorporating computational approaches that are essential for future careers in science, technology, engineering, and mathematics (STEM). The paper is based on theoretical and experimental research that addresses the integration of algorithms with traditional mathematical topics, such as algebra, geometry, and calculus, explaining how these approaches can help develop complex problem-solving skills. The research includes an analysis of international educational practices where algorithms have been successfully integrated into mathematics courses, including the use of tools such as Python, Scratch, and pseudocode to teach the concept of functions, data structures, and various algorithmic models. Furthermore, the study highlights the benefits of such teaching in fostering interdisciplinary thinking in fields such as computer science, engineering, and the natural sciences. The results show that students exposed to algorithms not only demonstrate a deeper understanding of mathematical concepts but also develop skills to address practical problems in a structured and innovative manner. This study also provides recommendations for teachers and curriculum designers for the effective implementation of algorithms in teaching, while maintaining a balance between traditional mathematics and contemporary technologies. In conclusion, incorporating algorithms into mathematics syllabus is an important step towards preparing the next generation for the digital and automated world, empowering students with skills that are essential for academic and professional success. The research has wide-ranging implications for education, pedagogy, and workforce development. By integrating algorithms into mathematics curricula, students develop skills that are essential for the digital economy, leading to more engaging learning experiences and improved academic performance. The study contributes both theoretically and practically to educational research and provides a solid foundation for future educational reforms in STEM disciplines